Atlas of pet-ct a quick guide to image interpretation - Fanti, Stefano (Springer Berlin Heidelberg, 2009)
This user-friendly atlas, featuring about 500 images, should be a quick guide to interpreting PET/CT images with FDG in oncology. It also illustrates how to recognize normal, para-physiological, and benign pathological uptakes in a case-based practical manner. The text, which includes most relevant technical and pathophysiological premises, covers the main clinical applications and clearly articulates learning points and pitfalls. This atlas aims to become a standard text for nuclear medicine physicians and radiologists, residents and technicians whose work involves PET/CT imaging. This book is also suitable for both undergraduate and postgraduate courses. Normal distribution of fdg - Contrast-enhanced ct in pet-ct (pet-cect) - Pitfalls in fdg pet-ct - Pet-ct in oncology.